DEVELOPMENT, CHARACTERIZATION AND IN VITRO RELEASE KINETIC STUDIES OF IBANDRONATE LOADED CHITOSAN NANOPARTICLES FOR EFFECTIVE MANAGEMENT OF OSTEOPOROSIS - PATHAK, S.; VYAS, S. P.; PANDEY, A. (International Journal of Applied Pharmaceutics, 2021)
Objective: The objective of the present study was to develop, optimize, and evaluate Ibandronate-sodium loaded chitosan nanoparticles (Ib-CS NPs) to treat osteoporosis. Methods: NPs were prepared by the Ionic gelation method and optimized for various parameters such as the effect of concentration of chitosan, sodium tripolyphosphate (TPP), and pH effect on particle size polydispersity index (PDI), zeta potential, and entrapment efficiency. The prepared nanoparticles were characterized using particle size analyzer (DLS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and Fourier-Transform Infrared spectroscopy (FTIR). Results: Formulated NPs were obtained in the average nano size in the range below 200 nm in TEM, SEM, and DLS studies. The particle size and encapsulation efficiency of the optimized formulation were 176.1 nm and 63.28%, respectively. The release profile of NPs was depended on the dissolution medium and followed the First-order release kinetics. Conclusion: Bisphosphonates are the most commonly prescribed drugs for treating osteoporosis in the US and many other countries, including India. Ibandronate is a widely used anti-osteoporosis drug, exhibits a strong inhibitory effect on bone resorption performed by osteoclast cells. Our results indicated that Ibandronate sodium-loaded chitosan nanoparticles provide an effective medication for the treatment of osteoporosis.